Coronary Artery Disease in Nepal: Current Perspective, Challenges, Need for National Practice Guidelines, and Potential Solution - Prajapati, D.; Bhandari, N.; Gautam, P.; Dhital, R.; Shrestha, A. (Kathmandu University Medical Journal, 2022)
South Asians are estimated to have a 40% increased risk for coronary artery disease as compared to populations from other regions. Nepal, as a South Asian country, should also analyze the burden of coronary artery disease and its risk factors to minimize cardiovascular morbidity and mortality. We reviewed the barriers to cardiovascular care and its services in low- and middle-income countries, including Nepal. The identified barriers included coronary artery disease risk factors, access, cost, adherence to cardiovascular care, awareness, knowledge gaps, and socioeconomic and health system challenges. The possible strategies to reduce coronary artery disease included national, regional, and local perspectives. It also highlighted the involvement of community workers and local leaders, education, patient-centered intervention, easy access to drugs and treatments, rehabilitation and public health measures, innovation within the health care system, and multi-sectoral involvement. This review provides insights into the current situation of coronary artery disease and its possible solutions.